LA PRACTICA DE VALORES Y EL IMPACTO EN EL COMPORTAMIENTO DE LOS(AS) ESTUDIANTES DE LOS DÉCIMOS AÑOS DE EDUCACIÓN BÁSICA DE LA UNIDAD EDUCATIVA COMPENSATORIO CATAMAYO - Riofrìo Martìnez, Marìa Fernanda (2015)
This thesis work entitled "The practical value and impact on behavior (as) students in say years of basic education of the Education Unit Compensatory Catamayo" made according to the provisions of the Academic Board of the University National Loja. General: match the need to achieve the following objectives has been to establish a strategy to promote the strengthening of values in practice to improve performance in the / os students "Compensatory Education Unit Catamayo." The specific objectives were: Basing theoretical notions and categories subject under study; Investigate the causes and limited practice of values that affects the behavior of the students say years Catamayo Compensatory Education Unit; Design a strategic participatory approach focused on strengthening the practice of values students Compensatory Education Unit Catamayo. Having verified that the practice of values is one of the causes and negative effects on student behavior that is difficult to have good relations within the school and where are educated; the overall objective research: Establish a strategy to promote the strengthening of values in practice to improve the performance of students "Compensatory Education Unit Catamayo" It has been able to establish the actions and identify theories regarding the issue that led to know better, to establish intervention strategies and provide alternative solutions to the causes that affects the limited practice of values and behavior, in which it activities run by the benefit to students, parents, teachers. The research was developed based on the scientific method and auxiliary as deductive, inductive, analytic, synthetic, statistical methods, with the object of study, to promote a higher level through the intervention of the social worker 6 and the implementation of strategies to appropriate to strengthen values and behavior in school. In the development of this study, using research tools, the necessary information both students, parents, teachers of the school were collected. Data after being processed and examined established as a result of the limited practice values cause negative effects on student behavior makes it difficult to have good peer relations, affecting the student be in a hostile environment and not allowed to develop in a way appropriate. It confirms that aggressive behavior, rebellion and discouragement affect the achievement of significant learning of the students who disturb their integration in the various recreational, sports and cultural activities in the place where they live. There are young people who live in dysfunctional homes, become clear that family breakdown is incident on the aggressive behavior of the same. These students become little emotional, restless, aggressive and violent which directly affects relationships with others. It has also identified the lack of knowledge about the role it can play a social worker in the school, as both teachers and parents and students are unaware of the functions that it can develop, and therefore the aid could bring in the behavior of young people. Finally it raised a proposal for participatory action concerning the intervention of social workers to students, parents and educational institution which implements the values to improve behavior and coexistence among peers and family.